Análise da eficiência energética e otimização de secadores rotativos - Leonel, Edimilson Cândido (2014)
Energy Efficiency and optimization of dryers are research areas with environmental concerns. These areas have the increasing need to improve the energy performance of processes through to quality improvement and reduction of production costs. In this sense, this work aims to contribute to the development of more efficient drying processes, take account the fact that this is one of the unit operations of higher energy consumption. Using a mathematical model for a direct-heating rotary dryer, computational simula¬tions were performed and the comparation with experimental results show that this model is reliable with the drying process. The model was implemented in order to simulate the rotary drier with concurrent and countercurrent feeding. Thus, the energetic differences between the two operations were compared and discussed. For the studies of the energy performance of rotary dryers, two definitions of Energy Efficiency were used: an expression quite common in the literature, and largely used in drying procedures, and another expression that was proposed from the observation of energetical quantities related to the process. The advantages and disadvantages of each defition are presented and the results contribute to the discussion on the assessment of Energy Efficiency in convective dryers. Parametric Sensitivity studies have quantified the influence that certain process va¬riables have on measures of Energy Efficiency and Final Moisture Content of Product. These results showed that these variables play an important role in both the Energy Ef¬ficiency and Final Moisture Content of Product, being necessary to establish appropriate operational limits to the range of variation to these variables, in order to satisfy the best operational conditions for the two rotary dryers. The results also showed significant dif¬ferences between concurrent and countercurrent operations. In addition, the Parametric Sensitivity analisys serve as a base for optimization studies. The results from the optimization of rotary dryers showed that is possible to im¬proving the Energy Efficiency without decrese the quality of the final product, and also the possibility of simultaneous improvement of both the Energy Efficiency as the Final Moisture Content of Product. It was possible to establish, for each dryer, mathematical relations between optimum Efficiency and desired Final Moisture Content of Product. These results are very interesting and represent an important contribution to the study of rotary dryers.